The Contribution of Thai Fisheries to Sustainable Seafood Consumption: National Trends and Future Projections - Tiptiwa Sampantamit; Long Ho; Carl Lachat; Giles Hanley-Cook; Peter Goethals (Foods, 2021)
Sustainably feeding a growing human population is one of the greatest food system challenges of the 21st century. Seafood plays a vital role in supporting human wellbeing, by providing bioavailable and nutrient-dense animal-source food. In Thailand, seafood demand is increasing, and wild capture fishery yields have plateaued, due to oceanic ecosystem degradation and fishery stock exploitation. In this study, we investigated the supply trend of fishery products and subsequent seafood-derived nutrient availability over the last decade. In addition, we explored the possibility of predicting seafood availability and consumption levels, including adherence to Thailand’s national food guide and global dietary recommendations for sustainable seafood consumption. Our findings indicate that, at national-level, fishery products supplied between 19% and 35% of the Thai populations recommended dietary protein intake, 4–6% of calcium, 6–11% of iron, and 2–4% of zinc from 1995 to 2015. Nevertheless, our research also reports that if Thailand’s wild-caught seafood production were to decrease by 13%, as is highly likely, by 2030, the country might face a per capita supply deficit of fish and shellfish to meet healthy and sustainable dietary recommendations (28–30 g/day), let alone the current Thai average intake (32 g/day). Although a 1% per year increase in aquaculture production might bridge this supply gap, policymakers and relevant fishery stakeholders must consider the long-term environmental impacts of such an approach in Thailand.